Analysis Of Cms-Integration Project Delays And Proposed Project Management Improvement At Len Defense Electronics (The Indonesian Journal of Business Administration, 2020)
Indonesia’s defense industry has improve over the year, various procurements are expected to increase in an effort to modernize its armed forces and support existing projects. This is anticipated to result in increased demand for maritime surveillance and security equipment. As part of this commitment, PT Len Industri (Persero) to present one of its best works, namely Combat Management System (CMS). Len as the SOE in defense sector supposed to hold this opportunity and keep in synergized conditions with other SOEs and private company. But in the mean time amount of CMS project which normally can be executed well starts resulting in a lot of project delay. Based on the problems, the objectives are to discover the root causes for CMS-Integration project delays and find the proposed solutions for minimizing the project delays.The research began with gathering information about the CMS-Integration project management process in Len. The process is done through observations, interviews and discussions for the constructs. Then the analysis was carried out to find the root cause of the CMS-Integration project delays using Current Reality Tree and then discussed with the company representatives.Results from root cause analysis shows from 34 UDEs there are 12 root cause problems for the project delays. However due to the limitations the research use pareto analysis in order to solve 80% of frequent problems mentioned by respondents and decide which problems need to be prioritized.There are 7 findings from Pareto analysis: lack of project prioritization, lack of project stakeholder interest accomodation, lack of project scope of work identification, lack of project design drawing accuracy, lack of project documentation system, lack of project engineering standard and standard to run the project. The proposed solutions then discussed and selected to solve the root causes. Each findings then classified in to their respective root cause category, because it has the similarity on how to solve the issues, there are 4 root categories that need to be prioritized. The proposed solutions, CMS-Integration project requires project management office to improve project approval system, and improve project business process that can cover management and engineering standard, project document control, scope and collect requirements. Keywords: CMS Integration Project, Current Reality Tree, Pareto Analysis, Project Management